Exploring Pedagogical Strategies: Integrating 21st-Century Skills in Science Classrooms - Esty Haryani; William W. Cobern; Brandy Ann-Skjold Pleasants; Marcia K. Fetters (Journal of Education in Science, Environment and Health)
Developing 21st-century skills among students is crucial for their success in college, future careers, and civic engagement. These skills, commonly referred to as the 4Cs (creativity, critical thinking and problem-solving, communication, and collaboration), require teachers to provide tailored learning experiences. This study investigates the factors influencing teachers' selection of pedagogical strategies to foster the integration of the 4Cs, their approach to lesson planning, and the actual implementation of these plans in the classroom. In this qualitative study, three chemistry teachers, self-reporting moderate 4C implementation, participated. Data were gathered through semi-structured interviews, analysis of lesson plans, and classroom observations. The findings reveal that teachers take into account student characteristics and learning facility availability when designing 4C-integrated lesson plans. Influencing factors include student attributes, the science topic, and teachers' mastery of the chosen approach. Communication, collaboration, and critical thinking emerge as the most integrated skills, with interactive lectures being the predominant teaching method. The study discusses the implications of these findings for educators and curriculum development.